Digital learning and student outcomes: a mathematical synthesis from the last decade - Koishybekova, Aizhan; Zhanatbekova, Nazym; Khaimuldanov, Yerlan; Orazbayeva, Assel; Abykenova, Dariya (Institute of Advanced Engineering and Science, 2025)
Understanding the broad effects of e-learning on educational outcomes and the contributing factors is crucial, especially given the conflicting conclusions from past research. This is important to ensure that educators and policymakers do not waste resources and focus effectively when prioritizing digital investments. Hence, this study sought to provide a comprehensive quantitative review of the extant evidence on how digital learning initiatives affect student outcomes within the cognitive domain across different subjects and educational levels. To that end, a meta-analysis was performed encompassing 17 studies spanning from 2015 to 2023, involving 1,896 participants. The quantitative synthesis was completed using a random-effects model. The results indicate a positive small to medium overall effect size (Hedge’s g=.49, adjusted for publication bias) for technology-assisted interventions compared to traditional education. Subgroup analyses revealed nuances, such as higher academic gains associated with active cognitive engagement modes and potential disparities between school and higher education settings. However, no factors significantly affected the pooled effect sizes for cognitive outcomes. Nevertheless, considerable between-study heterogeneity could compromise the estimates. The meta-analysis underscores the scarcity of rigorous studies in the digital learning domain. Further research directions are outlined.